Salt-water Heater - Balqis Husni; Liyana Amalina Adnan; Muhammad Amirul Firdaus Muhammad Ariff; Yahaya Basiron (Kolej Genius Insan, Universiti Sains Islam Malaysia, 2024)
2nd Insan Junior Researchers International Conference 2021 (iJURECON 2021) “STREAM for a Better Life” 15-17th October 2021 Organized By :Kolej GENIUS Insan of Universiti Sains Islam Malaysia